Are family warmth and positive remarks related to outcomes in psychosis? A systematic review. Issue 8 (20th December 2018) - Butler, Rebecca; Berry, Katherine; Varese, Filippo; Bucci, Sandra
Abstract: Background: Affective attitudes and behaviours manifested within the family environment have been characterised as expressed emotion (EE). High EE environments have been robustly shown to put psychosis patients at a greater risk of relapse compared with low EE exposure. Positive EE dimensions (warmth; positive remarks) have received far less attention than negative EE dimensions such that EE has become synonymous with a negative family atmosphere; the predictive value of positive EE dimensions is largely ignored. A systematic review examining the relationship between positive family EE and outcomes in psychosis is needed. Methods: A systematic search was conducted. Studies reporting bias and study quality were assessed. Results: A total of 2368 studies were identified. Of these, 27 met eligibility criteria reporting outcomes including relapse, symptomatology, social functioning and life satisfaction. Relapse was the most commonly measured outcome. Stronger evidence emerged for the association between EE warmth and outcomes compared with EE positive remarks, with effects mostly evident in the early phase of psychosis. Evidence for protective effects of warmth on relapse was found up to 9 months follow-up. No effects were evident between positive remarks and relapse. Studies assessing symptom outcomes showed inconsistent findings. Evidence for an association with social functioning was evident, primarily in at risk mental states. Warmth and positive remarks predicted life satisfaction. Conclusions: The positive aspects of EE require further investigation with longitudinal research designs. Clinical interventions should focus not only on reducing negative aspects of EE but also foster warmth within families in the context of psychosis.